2015
DOI: 10.1073/pnas.1505748112
|View full text |Cite
|
Sign up to set email alerts
|

Diverse set of Turing nanopatterns coat corneae across insect lineages

Abstract: Nipple-like nanostructures covering the corneal surfaces of moths, butterflies, and Drosophila have been studied by electron and atomic force microscopy, and their antireflective properties have been described. In contrast, corneal nanostructures of the majority of other insect orders have either been unexamined or examined by methods that did not allow precise morphological characterization. Here we provide a comprehensive analysis of corneal surfaces in 23 insect orders, revealing a rich diversity of insect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(124 citation statements)
references
References 37 publications
5
113
0
Order By: Relevance
“…Another interesting attribute of Turing patterns is that they can be obtained on a wide variety of scales ranging from the nanoscale to the macroscopic scale. Patterns can be observed in leaves of plants and nano-Turing patterns were recently observed in the corneas of different arthropods (Blagodatski, et al, 2015), Figure 3a; microscopic analysis of corneas from different insect families showed that there is a certain correlation between families with similar evolutionary origins and the morphology of the observed pattern, enabling entomology to consider a new taxonomic criterion.…”
Section: Pattern Formation At All Scales: Main Featuresmentioning
confidence: 87%
See 1 more Smart Citation
“…Another interesting attribute of Turing patterns is that they can be obtained on a wide variety of scales ranging from the nanoscale to the macroscopic scale. Patterns can be observed in leaves of plants and nano-Turing patterns were recently observed in the corneas of different arthropods (Blagodatski, et al, 2015), Figure 3a; microscopic analysis of corneas from different insect families showed that there is a certain correlation between families with similar evolutionary origins and the morphology of the observed pattern, enabling entomology to consider a new taxonomic criterion.…”
Section: Pattern Formation At All Scales: Main Featuresmentioning
confidence: 87%
“…Thus, the presence of patterns in living beings can be indicators of their evolutionary history and their adaptability, as suggested by some recent studies (Blagodatski, et al, 2015). Regarding inert systems, pattern formation results in the design of efficient bio-inspired technologies, in particular the design of structured-surface solids with appropriate patterns for specific applications (Bensemann, et al, 2005) and the design of chemical processes that emulate organic systems of living beings, such as the respiratory and circulatory systems (Coppens, 2012) …”
Section: What Advantages Do Static Patterns Bring To the System?mentioning
confidence: 96%
“…This is particularly true for insects living in low-light conditions, such as moths and other nocturnal insects, which feature similar nanopillars covering their facet lenses ( Figure 15C,D). [342][343][344][345] These so-called corneal nipple arrays optimize light flux into the eye and photon detection by the photoreceptors. As a positive side effect, the surface reflection of the eyes is minimized during daytime, suppressing a detectable reflection of the inactive insects by predators.…”
Section: Transparencymentioning
confidence: 99%
“…[332] Copyright 2014, Matteo Burresi. nanostructures ( Figure 15E) whose developmental pathway is unknown but is hypothesized to be based on a Turing-like patterning of the outermost corneal layer during development. [344] …”
Section: Transparencymentioning
confidence: 99%
“…1C). Turing systems are thought to underlie many different examples of developmental patterning, including mesendodermal and left-right organization (Müller et al, 2012), mammalian palatal rugal ridge formation (Economou et al, 2012), hair follicle spacing (Sick et al, 2006), finger formation (Raspopovic et al, 2014) and nano-features of insect cornea (Blagodatskia et al, 2015).…”
Section: Box 1 Glossarymentioning
confidence: 99%